Transcriptomic analysis of oriental tea tortrix infected with male-killing virus - Takumi Takamatsu; Xiaonan Xie; Maki N. Inoue (Molecular Biology Reports, 2026)

Large-scale field sampling reveals non-male killing Spiroplasma infection in Lymantria umbrosa in Hokkaido, Japan - Kyoko Ishida; Maki N. Inoue; Masataka G. Suzuki (Symbiosis, 2026)

Nivicolous myxomycetes in the French Pyrenees – A biodiversity study aided by two molecular markers - Pauline Hampe; Ángela López-Villalba; Maho Inoue; Oleg N. Shchepin; Jan Woyzichovski; Flavius Popa; Martin Schnittler (Protist, 2025)

Modelling free residual chlorine decay in a residential district water distribution network using smart water meter data - S. Obaid; K. Hosoi; N. M. Ngoc; T. Inoue; K. Yokota (International Journal of Environmental Science and Technology, 2025)
Chlorine is the most common disinfectant in drinking water worldwide, and the free residual chlorine concentration has been stipulated at least 0.1 mg/L according to Japanese drinking water standard to ensure disinfection efficacy during distribution. In addition, Japan is also applying approximately 0.4 mg/L chlorine at treatment plants to supply tasty drinkable water to residents. Although a concentration lower than 0.4 mg/L can help avoid an unpleasant chlorine taste in the supply water, it raises challenges for maintaining residual chlorine greater than the standard throughout distribution pipelines. The chlorine concentration decreases along distribution pipes because of bulk decay and wall decay. These decays depend on the initial chlorine concentration, temperature, time, pipe material, etc. Therefore, bottle tests with the Arrhenius theory were set up on the water at the distribution inlet in the Chibata district in Kosai city, Japan at various temperatures and times to measure the bulk decay coefficient. A literature review and root square mean error matching field data were conducted to estimate the wall decay coefficient. These decay coefficients were input into EPANET 2.2 to simulate water quality using smart water meters’ hourly consumption data. Therefore, the points where chlorine concentrations were below the standard could be hourly estimated.

Correction to: Integration of satellite remote sensing and MaxEnt modeling for improved detection and management of forest pests - Natsumi Mori; Megumi Yamashita; Maki N. Inoue (Environmental Monitoring and Assessment, 2024)

Monitoring and prediction of the spongy moth (Lymantria dispar) outbreaks in Mountain’s landscape using a combination of Sentinel-2 images and nonlinear time series model - Natsumi Mori; Kazutaka Kawatsu; Suzuki Noriyuki; Aleksey Kosilov; Vyacheslav Martemyanov; Megumi Yamashita; Maki N. Inoue (Forest Ecology and Management, 2024)

Integration of satellite remote sensing and MaxEnt modeling for improved detection and management of forest pests - Natsumi Mori; Megumi Yamashita; Maki N. Inoue (Environmental Monitoring and Assessment, 2024)

Polyandry may mitigate the negative impact of reproductive interference among bumblebees in Japan - Fumina Inokuchi; Maki N. Inoue; Yuya Kanbe; Masaaki Ito; Jun-ichi Takahashi; Tetsuro Nomura; Koichi Goka; Koji Tsuchida (The Science of Nature, 2024)
In social hymenopterans, monandry of the queen is an ancestral trait, and polyandry is a derived trait. Polyandry of the queen is the norm in a limited number of lineages, such as honeybees, leaf-cutting ants, Pogonomyrmex ants, and Vespula wasps, which presumably provide fitness advantages for the whole colony. The queen of the introduced bumblebee, Bombus terrestris , is polyandrous in Japan, whereas it is monandrous in native regions. We hypothesize that polyandry can evolve in a process that avoids the negative impacts of reproductive interference caused by interspecific mating and conducted genetic studies of the invasive species B. terrestris and two native subspecies, Bombus hypocrita sapporoensis and Bombus hypocrita hypocrita , in Japan. Our results revealed that although the native queens of B. hypocrita hypocrita allopatric with B. terrestris were strictly monandrous, the native queens of B. hypocrita sapporoensis sympatric with B. terrestris were polyandrous. These results suggested that the queens of native B. hypocrita sapporoensis do not experience negative impacts on interspecific mating from the invasive B. terrestris . We discuss the possibility that reproductive interference is a driving force in selection for multiple mating through an arms race between sympatric species.

DNA barcodes reliably differentiate between nivicolous species of Diderma (Myxomycetes, Amoebozoa) and reveal regional differences within Eurasia - Oleg N. Shchepin; Ángela López Villalba; Maho Inoue; Ilya S. Prikhodko; Daria A. Erastova; Mikhail V. Okun; Jan Woyzichovski; Yuka Yajima; Vladimir I. Gmoshinskiy; Gabriel Moreno; Yuri K. Novozhilov; Martin Schnittler (Protist, 2024)

P03-12: In vivo mutagenicity assessment and derivation of reference dose of styrene - Y. Murata; M. Matsumoto; T. Iso; Y. Shigeta; S. Hasegawa; T. Umano; N. Hirose; K. Horibata; K.-I. Sugiyama; K. Inoue; A. Hirose; K. Masumura (Toxicology Letters, 2023)

Phylogenetic and population genetic analyses of plantago asiatica mosaic virus isolates reveal intraspecific diversification - Minako Furuya; Shino Tanai; Islam Hamim; Yuna Yamamoto; Haruki Abe; Kazuho Imai; Hiroki Saito; Kazuo Yamashita; Tamaki Uehara-Ichiki; Kaoru Hanada; Tatsuya Kon; Maki N. Inoue; et al. (Journal of General Plant Pathology, 2023)

Genetic effects of demographic bottleneck and recovery in Kinkazan Island and mainland populations of Japanese macaques (Macaca fuscata) - N. Kazahari; E. Inoue; N. Nakagawa; Y. Kawamoto; T. Uno; M. Inoue-Murayama (Primates, 2023)

Distribution of brain oxytocin and vasopressin V1a receptors in chimpanzees (Pan troglodytes): comparison with humans and other primate species - Christina N. Rogers Flattery; Daniel J. Coppeto; Kiyoshi Inoue; James K. Rilling; Todd M. Preuss; Larry J. Young (Brain Structure and Function, 2022)

Variability in the Net Ecosystem Productivity (NEP) of Seaweed Farms - Yoichi Sato; Gregory N. Nishihara; Atsuko Tanaka; Dominic F. C. Belleza; Azusa Kawate; Yukio Inoue; Kenjiro Hinode; Yuhei Matsuda; Shinichiro Tanimae; Kandai Tozaki; Ryuta Terada; Hikaru Endo (Frontiers in Marine Science, 2022)
The important role of vegetated ecosystems in the sequestration of carbon has gained strong interest across a wide variety of disciplines. With evidence growing of the potential for macroalgae ecosystems to capture carbon, there is burgeoning interest in applying newfound knowledge of carbon capture rates to better understand the potential for carbon sequestration. Seaweed farms are expected to play a significant role in carbon capture; advocates for the expansion of seaweed farms are increasing in many countries. In general, seaweed farms are expected to be highly productive, although whether they are autotrophic or heterotrophic ecosystems and hence potential exporters of carbon, is under debate. Therefore, we present our investigation of three seaweed farms, two in northern Japan and one in southern Japan. We examine the frequency of autotrophic days and compare potential rates of carbon capture of the seaweed farms with two natural macroalgae ecosystems and one degraded site. We estimated potential carbon capture rates by calculating the net ecosystem productivity from continuous recordings of dissolved oxygen concentrations under natural environmental conditions. The net ecosystem production rates for the natural ecosystems in Arikawa Bay and Omura Bay were equivalent to 0.043 and 0.054 [g C m -2 d -1 ] m -1 , respectively. Whereas, for the degraded ecosystem in Tainoura Bay, it was -0.01 [g C m -2 d -1 ] m -1 . We reveal that the Undaria pinnatifida farm in Matsushima Bay experience autotrophy more often than natural ecosystems, although for seaweed farms producing U. pinnatifida in Hirota Bay and Cladospihon okamuranus at Bise Point, autotrophy was less frequently observed. Nevertheless, up to 14.1 g C m -2 (0.110 g C m -2 d -1 ) was captured by the production of U. pinnatifida and 3.6 g C m -2 (0.034 g C m -2 d -1 ) was captured by C. okamuranus , and the total yield of carbon captured during 2021 production season for these farms was 43,385 kg C.

Eccrine sweat glands’ maximum ion reabsorption rates during passive heating in older adults (50–84 years) - N. Gerrett; T. Amano; Y. Inoue; Narihiko Kondo (European Journal of Applied Physiology, 2021)

Area-wide insecticide resistance and endosymbiont incidence in the whitefly Bemisia tabaci MEAM1 (B biotype): A Neotropical context - R. A. C. Dângelo; M. Michereff-Filho; A. K. Inoue-Nagata; P. S. da Silva; M. Chediak; R. N. C. Guedes (Ecotoxicology, 2021)

The effects of Nosema ceranae (Microspora: Nosematidae) isolated from wild Apis cerana japonica (Hymenoptera: Apidae) on Apis mellifera - Yuki Hosaka; Yuto Kato; Shinya Hayashi; Madoka Nakai; Seth M. Barribeau; Maki N. Inoue (Applied Entomology and Zoology, 2021)

The influence of local skin temperature on the sweat glands maximum ion reabsorption rate - N. Gerrett; T. Amano; G. Havenith; Y. Inoue; Narihiko Kondo (European Journal of Applied Physiology, 2019)

Spatial variation in low-level 134Cs in the coastal sediments off central Honshu in the Sea of Japan: implications for delivery, migration, and redistribution patterns - Mutsuo Inoue; H. Uemura; H. Kofuji; K. Fujimoto; H. Takata; Y. Shirotani; N. Kudo; S. Nagao (Journal of Oceanography, 2017)

Effect of granulovirus infection of Spodoptera litura (Lepidoptera: Noctuidae) larvae on development of the endoparasitoid Chelonus inanitus (Hymenoptera: Braconidae) - Asadullah Azam; Yasuhisa Kunimi; Maki N. Inoue; Madoka Nakai (Applied Entomology and Zoology, 2016)

Different acute toxicity of fipronil baits on invasive Linepithema humile supercolonies and some non-target ground arthropods - Daisuke Hayasaka; Naoki Kuwayama; Azuma Takeo; Takanobu Ishida; Hiroyuki Mano; Maki N. Inoue; Takashi Nagai; Francisco Sánchez-Bayo; Koichi Goka; Takuo Sawahata (Ecotoxicology, 2015)

Ecological impacts on native ant and ground-dwelling animal communities through Argentine ant (Linepithema humile) (Hymenoptera: Formicidae) management in Japan - Maki N. Inoue; Fuki Saito-Morooka; Kazutaka Suzuki; Takuji Nomura; Daisuke Hayasaka; Toshio Kishimoto; Katsuo Sugimaru; Takashi Sugiyama; Koichi Goka (Applied Entomology and Zoology, 2015)

Identification and characterization of 12 microsatellite loci for Physa in the Chihuahuan Desert - Kofi N. Ansah; Kentaro Inoue; Brian K. Lang; David J. Berg (Conservation Genetics Resources, 2014)

Analyzing flood risk and related impacts to urban communities in central Vietnam - Bam H. N. Razafindrabe; Ryohei Kada; Makoto Arima; Shoji Inoue (Mitigation and Adaptation Strategies for Global Change, 2014)

The effect of light and temperature on the growth and photosynthesis of Gracilariopsis chorda (Gracilariales, Rhodophtya) from geographically separated locations of Japan - Ryuta Terada; Shingo Inoue; Gregory N. Nishihara (Journal of Applied Phycology, 2013)

Complete genome sequence of arracacha mottle virus - Anelise F. Orílio; Natalia Lucinda; André N. Dusi; Tatsuya Nagata; Alice K. Inoue-Nagata (Archives of Virology, 2013)

Potential increase in mating frequency of queens in feral colonies of Bombus terrestris introduced into Japan - Maki N. Inoue; Fuki Saito; Koji Tsuchida; Koichi Goka (The Science of Nature, 2012)

Complete genome sequence of pepper yellow mosaic virus, a potyvirus, occurring in Brazil - N. Lucinda; W. B. da Rocha; A. K. Inoue-Nagata; T. Nagata (Archives of Virology, 2012)

Holocene uplifted coral reefs in Lanyu and Lutao Islands to the southeast of Taiwan - S. Inoue; H. Kayanne; N. Matta; W. S. Chen; Y. Ikeda (Coral Reefs, 2011)

Search in Solanum (section Lycopersicon) germplasm for sources of broad-spectrum resistance to four Tospovirus species - É. C. Dianese; M. E. N. Fonseca; A. K. Inoue-Nagata; R. O. Resende; L. S. Boiteux (Euphytica, 2011)

Colony growth and reproductive ability of feral nests of the introduced bumblebee Bombus terrestris in northern Japan - M. N. Inoue; J. Yokoyama; K. Tsuchida (Insectes Sociaux, 2010)

The role of forest stand density in controlling soil erosion: implications to sediment-related disasters in Japan - Bam H. N. Razafindrabe; Bin He; Shoji Inoue; Tsugio Ezaki; Rajib Shaw (Environmental Monitoring and Assessment, 2010)

Characterization of a member of a new Potyvirus species infecting arracacha in Brazil - A. F. Orílio; A. N. Dusi; N. R. Madeira; Alice Kazuko Inoue-Nagata (Archives of Virology, 2009)

Brugmansia suaveolens mottle virus, a novel potyvirus causing leaf mottling of Brugmansia suaveolens in Brazil - N. Lucinda; T. Nagata; A. K. Inoue-Nagata; R. B. Salaroli; E. W. Kitajima (Archives of Virology, 2008)

Changes in fire regimes since the Last Glacial Maximum: an assessment based on a global synthesis and analysis of charcoal data - M. J. Power; J. Marlon; N. Ortiz; P. J. Bartlein; S. P. Harrison; F. E. Mayle; A. Ballouche; R. H. W. Bradshaw; C. Carcaillet; C. Cordova; S. Mooney; P. I. Moreno; et al. (Climate Dynamics, 2008)

Displacement of Japanese native bumblebees by the recently introduced Bombus terrestris (L.) (Hymenoptera: Apidae) - Maki N. Inoue; Jun Yokoyama; Izumi Washitani (Journal of Insect Conservation, 2008)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Fluctuating serotonergic function in premenstrual dysphoric disorder and premenstrual syndrome: findings from neuroendocrine challenge tests - Y. Inoue; T. Terao; N. Iwata; K. Okamoto; H. Kojima; T. Okamoto; R. Yoshimura; J. Nakamura (Psychopharmacology, 2006)

Development of Stable Isotope Dilution Quantification Liquid Chromatography–Mass Spectrometry Method for Estimation of Exposure Levels of Bisphenol A, 4-tert-Octylphenol, 4-Nonylphenol, Tetrabromobisphenol A, and Pentachlorophenol in Indoor Air - K. Inoue; S. Yoshida; S. Nakayama; R. Ito; N. Okanouchi; H. Nakazawa (Archives of Environmental Contamination and Toxicology, 2006)

Expression of foreign type I ribulose-1,5-bisphosphate carboxylase/ oxygenase (EC 4.1.1.39) stimulates photosynthesis in cyanobacterium Synechococcus PCC7942 cells - T. Iwaki; K. Haranoh; N. Inoue; K. Kojima; R. Satoh; T. Nishino; S. Wada; H. Ihara; S. Tsuyama; H. Kobayashi; A. Wadano (Photosynthesis Research, 2006)

Intracolony variation of bacterial gut microbiota among castes and ages in the fungus‐growing termite Macrotermes gilvus - Y. HONGOH; L. EKPORNPRASIT; T. INOUE; S. MORIYA; S. TRAKULNALEAMSAI; M. OHKUMA; N. NOPARATNARAPORN; T. KUDO (Molecular Ecology, 2006)
The fungus‐growing termites Macrotermes cultivate the obligate ectosymbiontic fungi, Termitomyces . While their relationship has been extesively studied, little is known about the gut bacterial symbionts, which also presumably play a crucial role for the nutrition of the termite host. In this study, we investigated the bacterial gut microbiota in two colonies of Macrotermes gilvus , and compared the diversity and community structure of bacteria among nine termite morphotypes, differing in caste and/or age, using terminal restriction fragment length polymorphism (T‐RFLP) and clonal analysis of 16S rRNA. The obtained molecular community profiles clustered by termite morphotype rather than by colony, and the clustering pattern was clearly more related to a difference in age than to caste. Thus, we suggest that the bacterial gut microbiota change in relation to the food of the termite, which comprises fallen leaves and the fungus nodules of Termitomyces in young workers, and leaves degraded by the fungi, in old workers. Despite these intracolony variations in bacterial gut microbiota, their T‐RFLP profiles formed a distinct cluster against those of the fungus garden, adjacent soil and guts of sympatric wood‐feeding termites, implying a consistency and uniqueness of gut microbiota in M. gilvus . Since many bacterial phylotypes from M. gilvus formed monophyletic clusters with those from distantly related termite species, we suggest that gut bacteria have co‐evolved with the termite host and form a microbiota specific to a termite taxonomic and/or feeding group, and furthermore, to caste and age within a termite species.

Assessment of room temperature influence on finger blood flow response induced by short-term grasping of vibrating handle - M. H. Mahbub; M. Inoue; K. Yokoyama; M. S. Laskar; H. Ohnari; K. Suizu; J. Inagaki; Y. Takahashi; N. Harada (International Archives of Occupational and Environmental Health, 2006)

Pharmacokinetics and pharmacodynamics of etizolam are influenced by polymorphic CYP2C19 activity - T. Fukasawa; N. Yasui–Furukori; A. Suzuki; Y. Inoue; T. Tateishi; K. Otani (European Journal of Clinical Pharmacology, 2005)

Effect of room temperature on percentage finger systolic blood pressure response to finger cooling - M. S. Laskar; K. Ohmura; M. Inoue; K. Yokoyama; J. Inagaki; Y. Takahashi; M. H. Mahbub; H. Ohnari; N. Harada (European Journal of Applied Physiology, 2005)

Sundasalanx (Sundasalangidae) is a progenetic clupeiform, not a closely‐related group of salangids (Osmeriformes): mitogenomic evidence - N. B. Ishiguro; M. Miya; J. G. Inoue; M. Nishida (Journal of Fish Biology, 2005)
Partitioned Bayesian analysis of whole mitochondrial genome sequences from 30 basal teleosts confidently placed Sundasalanx (Sundasalangidae) within the Clupeiformes, not Osmeriformes as originally thought. This study represents the first demonstration of the phylogenetic position of Sundasalanx on a phylogenetic tree.

Effect of skin temperature on the ion reabsorption capacity of sweat glands during exercise in humans - A. K. M. Shamsuddin; T. Kuwahara; A. Oue; C. Nomura; S. Koga; Y. Inoue; N. Kondo (European Journal of Applied Physiology, 2005)

Induction of the metabolism of etizolam by carbamazepine in humans - S. Kondo; T. Fukasawa; N. Yasui-Furukori; T. Aoshima; A. Suzuki; Y. Inoue; T. Tateishi; K. Otani (European Journal of Clinical Pharmacology, 2005)

Findings through the AsiaFlux network and a view toward the future - S. Yamamoto; N. Saigusa; M. Gamo; Y. Fujinuma; G. Inoue; T. Hirano (Journal of Geographical Sciences, 2005)

Changes in Activities of Enzymes Related to Energy Metabolism in Peripheral Leukocytes of Fattening Steers - N. Kimura; I. Yoshimura; T. Sako; A. Inoue; K. Tadami; T. Arai (Veterinary Research Communications, 2005)

A novel antipsychotic, perospirone, has antiserotonergic and antidopaminergic effects in human brain: findings from neuroendocrine challenge tests - M. Iwakawa; T. Terao; A. Soya; H. Kojima; Y. Inoue; N. Ueda; R. Yoshimura; J. Nakamura (Psychopharmacology, 2004)

Inhibition of the metabolism of etizolam by itraconazole in humans: evidence for the involvement of CYP3A4 in etizolam metabolism - K. Araki; N. Yasui-Furukori; T. Fukasawa; T. Aoshima; A. Suzuki; Y. Inoue; T. Tateishi; K. Otani (European Journal of Clinical Pharmacology, 2004)

Augmented cytoplasmic Smad4 induces acceleration of TGF-?1 signaling in renal tubulointerstitial cells of hereditary nephrotic ICGN mice with chronic renal fibrosis; possible role for myofibroblastic differentiation - Y. Goto; N. Manabe; K. Uchio-Yamada; M. Yamaguchi-Yamada; N. Inoue; Y. Yamamoto; A. Ogura; N. Nagano; H. Miyamoto (Cell and Tissue Research, 2004)

Perfluorooctane Sulfonate Contamination of Drinking Water in the Tama River, Japan: Estimated Effects on Resident Serum Levels - K. Harada; N. Saito; K. Sasaki; K. Inoue; A. Koizumi (Bulletin of Environmental Contamination and Toxicology, 2003)

Involvement of microtubules in rhizoid differentiation of Spirogyra species - K. Yoshida; N. Inoue; S. Sonobe; T. Shimmen (Protoplasma, 2003)

The effects of histamine on the lipopolysaccharide-induced metallothionein-I mRNA expression in the mouse spleen - T. Inoue; M. Nakano; N. Oda; T. Yoneyama; Y. Okano; K. Onodera; H. Furuta; C. A. Sogawa; N. Sogawa (Inflammation Research, 2003)

RECONSTRUCTION OF TUBULAR STRUCTURES IN THREE-DIMENSIONAL COLLAGEN GEL CULTURE USING PROXIMAL TUBULAR EPITHELIAL CELLS VOIDED IN HUMAN URINE - CHIYOKO N. INOUE; NORIO SUNAGAWA; TETSUJI MORIMOTO; SHOKO OHNUMA; FUMIO KATSUSHIMA; TOSHIYUKI NISHIO; YOSHIAKI KONDO; KAZUIE IINUMA (In Vitro Cellular & Developmental Biology - Animal, 2003)

Pepper yellow mosaic virus, a new potyvirus in sweetpepper, Capsicum annuum - A. K. Inoue-Nagata; M. E. N. Fonseca; R. O. Resende; L. S. Boiteux; D. C. Monte; A. N. Dusi; A. C. de ávila; R. A. A. van der Vlugt (Archives of Virology, 2002)

Genetic identification of two distinct DNA polymerases, DnaE and PolC, that are essential for chromosomal DNA replication in Staphylococcus aureus - R. Inoue; C. Kaito; M. Tanabe; K. Kamura; N. Akimitsu; K. Sekimizu (Molecular Genetics and Genomics, 2001)

Relationships among Nicotiana species revealed by the 5S rDNA spacer sequence and fluorescence in situ hybridization - S. Kitamura; M. Inoue; N. Shikazono; A. Tanaka (Theoretical and Applied Genetics, 2001)

Karyotype analysis of Nicotiana kawakamii Y. Ohashi using DAPI banding and rDNA FISH - R. Nakamura; S. Kitamura; M. Inoue; N. Ohmido; K. Fukui (Theoretical and Applied Genetics, 2001)

Ecological Evaluation of Gadolinium Toxicity Compared with Other Heavy Metals Using an Aquatic Microcosm - S. Fuma; H. Takeda; K. Miyamoto; K. Yanagisawa; Y. Inoue; N. Ishii; K. Sugai; C. Ishii; Z. Kawabata (Bulletin of Environmental Contamination and Toxicology, 2001)

Quantitative chromosome maps and rDNA localization in the T subgenome of Nicotiana tabacum L. and its putative progenitors - S. Kitamura; M. Inoue; N. Ohmido; K. Fukui (Theoretical and Applied Genetics, 2000)

Simple Aquatic Microcosm for Ecotoxicity Screening at the Community Level - S. Fuma; H. Takeda; K. Miyamoto; K. Yanagisawa; Y. Inoue; N. Ishii; K. Sugai; C. Ishii; Z. Kawabata (Bulletin of Environmental Contamination and Toxicology, 2000)

Determination of the phase boundary between ilmenite and perovskite in MgSiO 3 by in situ X-ray diffraction and quench experiments - K. Kuroda; T. Irifune; T. Inoue; N. Nishiyama; M. Miyashita; K. Funakoshi; W. Utsumi (Physics and Chemistry of Minerals, 2000)

Subsite-specific risk factors for hypopharyngeal and esophageal cancer (Japan) - T. Takezaki; M. Shinoda; S. Hatooka; Y. Hasegawa; S. Nakamura; K. Hirose; M. Inoue; N. Hamajima; T. Kuroishi; H. Matsuura; K. Tajima (Cancer Causes & Control, 2000)

Symposia lectures - F. Parak; A. Ostermann; G. U. Nienhaus; Nobuo Niimura; William A. Eaton; Stephen J. Hagen; Eric R. Henry; James Hofrichter; Gouri Jas; Lisa Lapidus; Victor Muñoz; Chih-chen Wang; et al. (Journal of Biosciences, 1999)

Short communicationRecovery from derangement of natural killer‐like activity of leucocytes due to Zn or Mn deficiency in rainbow trout, Oncorhynchus mykiss (Walbaum), by the oral administration of these elements - M Inoue; S Satoh; M Maita; V Kiron; N Okamoto (Journal of Fish Diseases, 1998)

Histopathological Changes Within the Testis Caused by Allyl Chloride Exposure in Mice - M. Zhao; M. Omura; S. Tokunaga; Y. Romero; N. Inoue (Bulletin of Environmental Contamination and Toxicology, 1998)

Tea and coffee consumption and the risk of digestive tract cancers: data from a comparative case-referent study in Japan - M. Inoue; K. Tajima; K. Hirose; N. Hamajima; T. Takezaki; T. Kuroishi; S. Tominaga (Cancer Causes & Control, 1998)

Effects of various factors including the CYP2D6 genotype and coadministration of flunitrazepam on the steady-state plasma concentrations of bromperidol and its reduced metabolite - A. Suzuki; K. Otani; K. Mihara; N. Yasui; T. Kondo; N. Tokinaga; H. Furukori; S. Kaneko; Y. Inoue; K. Hayashi (Psychopharmacology, 1998)

Interaction between carbamazepine and bromperidol - K. Otani; M. Ishida; N. Yasui; T. Kondo; K. Mihara; A. Suzuki; H. Furukori; S. Kaneko; Y. Inoue (European Journal of Clinical Pharmacology, 1997)

Physical and genetic maps of the human herpesvirus 7 strain SB genome - G. Dominguez; J. B. Black; F. R. Stamey; N. Inoue; P. E. Pellett (Archives of Virology, 1996)

Restriction endonuclease mapping and molecular cloning of the human herpesvirus 6 variant B strain Z29 genome - G. J. Lindquester; N. Inoue; R. D. Allen; J. W. Castelli; F. R. Stamey; T. R. Dambaugh; J. J. O'Brian; R. M. Danovich; N. Frenkel; P. E. Pellett (Archives of Virology, 1996)

Replication of rat coronavirus in a rat cell line, LBC - N. Hirano; K. Ono; Y. Sada; A. Inoue; T. Murakami; H. Takamaru (Archives of Virology, 1985)